Analisis Faktor Pemilihan Jajanan, Kontribusi Gizi dan Status Gizi Siswa Sekolah Dasar - Dwikani Oklita Anggiruling; Ikeu Ekayanti; Ali Khomsan (Media Kesehatan Masyarakat Indonesia, 2019)
Fulfillment children’s nutritional needs is important to support growth and development. The dietary habitof school-age children which tends to prefer snacks at school rather than eating at homewill affect the nutritionalstatus of children. The purpose of this study was to analyze determinant factors of snacks choice, relationshipbetween snacks choice with frequency of snacks, and relationship of nutrition contribution of snacks with nutritionalstatus of children. This study was a cross-sectional study funded by the Neys-van Hoogstraten Foundation, theNetherlands and was conducted at three primary schools namely SDN Kedokan, SDN Pajajaran and SDN Cibogoin Cisauk Sub-District, Tangerang Regency with total subjects of this study were 109 students. Factor-analysisandRank Spearman relationship tests were used to analyze data. There are five main factors that determine thesnackschoice, namely familiarity factor, characteristics of snacks, environmental and social, nutritional content and variation,and health. Health factors and snack characteristics had significant relationships with frequency of snacks(p<0.05). The contribution of energy, protein, fat and carbohydrate had significant relationships with the nutritionalstatus of children (p<0.05). The study resultshows that snack choice played an important role in snackinghabits and nutrition contribution of snacks had an impact on nutritional status of children, therefore availability ofsnacks at school should consider the children’s snack choice and nutritioncontribution of snacks.